Alcoholic Cardiomyopathy: A Literature Review - Zurohidah, Aina; Al Hajiri, Aufar Zimamuz Zaman; Silaban, Rusdiana; Putri, Mutiara Aswar Eka; Mafruroh, Ilfia Hajar; Syarifah, Mustika Chasanatusy (Jurnal Medis Islam Internasional, 2022)
Background: Cardiomyopathy is a heart muscle disorder so which the heart cannot contract optimally. Alcoholic cardiomyopathy is a type of cardiomyopathy that dilates due to long-term alcohol consumption. The prevalence of alcoholic cardiomyopathy is higher in men than women. The age group with the most alcoholic cardiomyopathy was 45 to 74 year. Death from alcoholic cardiomyopathy had an autopsy result marked muscle dilatation. A toxicological examination can show the level of alcohol consumed. The cause of death in alcoholic cardiomyopathy is muscle dilatation due to chronic ethanol abuse. Islam expressly forbids something that makes losing mind, like alcohol. Alcohol has many disadvantages for the consumer in the form of loss of mind and turning away from Allah. Objective: This report aims to learn more about the definition, pathophysiology, clinical manifestation, and treatment of Alcoholic Cardiomyopathy. Also, Knowing and explaining Alcoholic Cardiomyopathy in terms of death and Islamic views. Methods: The design of this research is a literature review or library review, which is a systematic, direct, and reproducible research method by identifying, evaluating, and synthesizing published research.  Result: Alcoholic cardiomyopathy is a clinical diagnosis made in a patient with a set of findings that include a history of excessive alcohol consumption, possible physical signs of alcohol abuse (e.g., parotid disease, telangiectasia or spider angiomata, altered mental status, cirrhosis), heart failure, and other evidence consistent with dilated cardiomyopathy. People who frequently consume alcohol can cause nutritional disorders, especially vitamin B1 deficiency can cause cardiomyopathy. Alcohol will also cause abnormalities in the structure and function of mitochondria in heart cells. These abnormalities include enlarged mitochondrial structure, decreased metabolism, lack of several enzymes decreased ion transport, increased calcium flow, glycogen accumulation, and decreased ATP production. Conclusion: Cardiomyopathy is a heart muscle function disorder characterized by the loss of the ability of the heart muscle to pump blood so that the blood supply is not optimal and results in death. The most common cause is chronic alcohol consumption, which causes dilatation of the heart muscle. At the same time, alcohol is an ingredient that is forbidden to be consumed by Muslims because of its more significant impact.